An Introduction to Media - Prateek Gupta (Journal of Advanced Research in Journalism & Mass Communication, 2021)
Mass Communication includes correspondence with the mass crowds and subsequently the name Mass Communication. At the point when we are thinking, it is intra-individual correspondence, when there is vis-à-vis discussion between two individuals it is relational correspondence, school talk or discourse would be an illustration of gathering correspondence, however there is another degree of correspondence when we read papers, magazines, tune in to Radio or stare at the TV. This would be called ’Mass Communication ’ as the message is reached to the majority through various media. How to cite this article: Gupta P. An Introduction to Media. J Adv Res Jrnl Mass Comm 2020; 7(4): 4-5.